Consumer Intention Shift in the Wake of Technological Disruption: The Case of Starlink and Loyalty Decline among IndiHome Users in Eastern Indonesia - Akbar, Akbar Silo; Uturestantix; Saragih, Andi Samuel (International Journal of Economics (IJEC), 2025)
This study investigates how consumers’ perceptions of price and product quality influence their intention to adopt Starlink, a satellite-based internet service, and how this intention mediates loyalty decline toward The existing provider IndiHome in Jayapura, Indonesia. Using a structured survey of 100 Internet users and path analysis via linear regression, the findings reveal that price perception has a positive and significant effect on usage intention, whereas product quality perception, unexpectedly, has a significant negative effect. Furthermore, the intention to adopt Starlink significantly eroded loyalty to IndiHome. Theoretically, this study extends our understanding of consumer migration in the context of disruptive innovation in underserved markets. We positthat intention is a behavioral signal of dissatisfaction in monopolized infrastructure sectors. Practically, this study offers a warning for incumbent telcos to reassess service quality, customer experience, and pricing strategies